Aspects of environmental comfort and sustainability in the built environment - Mello, Alexandre Effori de (Periódico Eletrônico Fórum Ambiental da Alta Paulista, 2021)
The objective of this article is to bring to discussion aspects of environmental comfort, built environment and sustainability, given the climate crisis and the urgency to find solutions to the issue. The concepts of ambience, quality of the built environment, environmental comfort and sustainable development are discussed, in addition to principles that can guide Architecture in its search for a built environment that preserves comfort through sustainability. The method used is bibliographical review, and the paper concludes by affirming that while it is not possible do determine the extent to which sustainability principles applied to the built environment can contribute to tackling the climate crisis, there is no other alternative.